Rumen degradation kinetics of coffee hulls treated with calcium oxide under aerobic or anaerobic conditions - Roseira, João P. S.; Garcia, Rasmo; da-Silveira, Tâmara C.; Veloso, Cristina M.; da-Silva, Thiago C.; da-Silva, Leandro D.; Ribeiro, Everton T. (Revista Colombiana de Ciencias Pecuarias, 2020)
Background: Coffee hulls obtained from dry processing, have the potential to be used in ruminant diets. Objective: To evaluate the chemical composition and in situ degradability of dry matter (DM) and neutral detergent fiber (NDF) of coffee hulls treated with calcium oxide (CaO) in different environmental conditions (EC). Methods: Coffee hulls were subjected to treatments distributed in a 2 × 2 factorial arrangement, consisting of two levels of CaO (0 and 5%, on a DM basis) and two environmental conditions (aerobiosis and anaerobiosis) in a completely randomized design with four replicates, totaling sixteen experimental units. Five-gram samples were incubated in the rumen of two male cattle for 0, 3, 6, 9, 12, 24, 48, 72, 96, and 120 h. Results: Regarding dry matter degradation kinetic parameters, except for fraction b, the potential and effective degradability was affected (p<0.05) by a CaO × EC interaction. As for estimated fiber degradation parameters, the potentially degradable fraction b was affected (p<0.05) by CaO and EC. Treatment with CaO increased fraction b in 4.08 percentage points. Conclusions: The use of CaO in the treatment of coffee hulls increases the effective and potential degradability of DM and reduces the undegradable fiber fraction. Anaerobic condition is the best environment for the treatment of coffee hulls with CaO.